Plastic ingestion by a generalist seabird on the coast of Uruguay. Issue 1 (15th June 2016) - Lenzi, Javier; Burgues, María Fernanda; Carrizo, Daniel; Machín, Emanuel; Teixeira-de Mello, Franco
Abstract: We analyzed plastic ingestion by Kelp Gull ( Larus dominicanus ) from 806 pellets collected between 2011 and 2013. Employing a Raman spectroscopy, we characterized those polymers used to produce the plastics ingested. Debris was recorded in 143 pellets (%FO = 17.7%, n = 202, 92.58 g). Plastic was found in 119 pellets (%FO = 83%) and non-plastic occurred in 56 pellets (%FO = 39%). The most important debris category was plastic film with 55.3% (n = 79). Plastic bags were observed in 19 pellets (%FO = 2.4%, weight = 25.02 g). Glass was the second most important component (%FO = 18.9%) followed by plastic fragments (%FO = 17.8%). Plastic debris represented the 65.3% of the debris fragments (n = 132, weight = 58.84 g), and was composed by polyethylene (52%), polypropylene (26%), polyamide (12%), polystyrene (6%), polyvinyl chloride (2%), and polyethylene terephthalate (2%). How plastics were obtained by gulls and the effects on individuals are discussed, as well as environmental considerations about plastic pollution on coastal environments. Highlights: One of four pellets regurgitated by Kelp Gull contained debris. Plastic film was the most important debris category ingested by Kelp Gull. The majority of the debris was composed by synthetic polymers. Polyethylene was the most important polymer found in Kelp Gull diet. Plastic debris comes from open sky landfills with no management.